ORGANIZATION OF CHEMISTRY LABORATORY ACTIVITIES BASED ON VIRTUAL REALITY (VR) - Yakhshiyev , Sherali (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article analyzes the theoretical and practical aspects of organizing chemistry laboratory activities based on virtual reality (VR) technologies. The study scientifically covers the impact of VR technologies on the educational process based on the theory of cognitive visualization and the immersive learning effect. It also examines the capabilities of Chemstr and other virtual laboratory programs, their role and effectiveness in teaching chemistry.